Use of phage display biopanning as a tool to design CAR-T cells against glioma stem cells - Potez, Marine; Snedal, Sebastian; She, Chunhua; Kim, Jongmyung; Thorner, Konrad; Tran, Timothy H.; Ramello, Maria Cecilia; Abate-Daga, Daniel; Liu, James K. C. (Frontiers in Oncology, 2023)
Glioblastoma (GBM) is both the most common and aggressive type of primary brain tumor, associated with high mortality rates and resistance to conventional therapy. Despite recent advancements in knowledge and molecular profiling, recurrence of GBM is nearly inevitable. This recurrence has been attributed to the presence of glioma stem cells (GSCs), a small fraction of cells resistant to standard-of-care treatments and capable of self-renewal and tumor initiation. Therefore, targeting these cancer stem cells will allow for the development of more effective therapeutic strategies against GBM. We have previously identified several 7-amino acid length peptides which specifically target GSCs through in vitro and in vivo phage display biopanning. We have combined two of these peptides to create a dual peptide construct (EV), and demonstrated its ability to bind GSCs in vitro and target intracranial GBM in mouse models. A peptide pull-down performed with peptide EV followed by mass spectrometry determined N-cadherin as the binding partner of our peptide, which was validated by enzyme-linked immunosorbent assay and surface plasmon resonance. To develop cytotoxic cellular products aimed at specifically targeting GSCs, chimeric antigen receptors (CARs) were engineered containing the peptide EV in place of the single-chain variable fragment (scFv) as the antigen-binding domain. EV CAR-transduced T cells demonstrated specific reactivity towards GSCs by production of interferon-gamma when exposed to GSCs, in addition to the induction of GSC-specific apoptosis as illustrated by Annexin-V staining. These results exemplify the use of phage display biopanning for the isolation of GSC-targeting peptides, and their potential application in the development of novel cytotoxic therapies for GBM.